Survival, Functional Capacity, and Quality of Life after Cardiac Surgery Followed by Long-Term Intensive Care Stay - Deschka, Heinz; Schreier, Romy; El-Ayoubi, Lemir; Erler, Stefan; Alken, Aiman; Wimmer-Greinecker, Gerhard (The Thoracic and Cardiovascular Surgeon, 2013)
Background The rising prevalence of multimorbid patients undergoing cardiac surgery often leads to prolonged postoperative intensive care unit (ICU) treatment. The fate of these patients after discharge is poorly investigated. This study is aimed to assess survival, functional outcome, and quality of life (QOL) in patients after an ICU stay of at least 5 days.Materials and Methods Between August 2009 and July 2010, 1,092 patients underwent various cardiac procedures. Of these patients, 119 required ICU treatment of at least 5 days. Preoperative characteristics as well as postoperative course were analyzed and the discharged patients were contacted after 1 year to gain information about survival, functional capacity, and QOL.Results European system for cardiac operative risk evaluation I of the patients was 22.3 ± 16.7. Mean ICU stay was 19 ± 20 days. Forty three patients (36.1%) died in the hospital, 1-year overall survival was 46.2%, and 1-year survival of the discharged patients was 72.4%. Barthel mobility index was 85, showing a satisfactory mobilization. QOL, assessed with short form 12 questionnaire, was comparable with the reference group.Conclusion Long-term ICU treatment after cardiac surgery is related to a high in-hospital and follow-up mortality. The physical and psychological recovery of the survivors is encouraging, justifying the extensive engagement of hospital resources.
Keywords: intensive care; outcomes (includes mortality and morbidity); quality of life; cardiac